Pemanfaatan Balita Sebagai Anak Jalanan Di Kota Makassar - Wahidah Zafira Nurdin; St. Junaeda (Rayhan Intermedia, 2023)
This study aims to determine (1) the driving factors for the presence of the use of toddlers as street children in Makassar City, (2) the impact of the presence of the use of toddlers as street children in Makassar City, (3) the anthropological relationship between development and the presence of the use of toddlers as street children in the City of Makassar. Macassar. The type of research used is descriptive research with qualitative data. Data collection techniques used are observation, interviews and documentation. The results of the study show that: (1) the driving factors for the use of toddlers as street children in Makassar City are poverty and mentality that cause family dysfunction, (2) the impact of the use of toddlers as street children in Makassar City can occur to individuals who relevant, social and cultural. The impact of the presence of the use of toddlers is to trigger crime rates, increase in unemployment, fade human values and form a pessimistic mindset, (3) the relationship between development anthropology and the presence of the use of toddlers as street children in Makassar City is where this will change the values and norms in society and make new mindsets and habits that exist as a result of poverty and the mentality of society that encourages the child's family to make an instant way to earn income by using toddlers as street children.